La evaluación formativa en el proceso de montaje conjunto 2017- ii de la licenciatura en educación artística con énfasis en danza y teatro de la Universidad Antonio Nariño (2018)
In the present work, the importance of the formative evaluation applied to the joint assembly process 2017-II, an artistic-pedagogical experience, in the students of the last semester of the career. The general objective is to demonstrate the importance of the formative evaluation in the joint assembly 2017 - II subject, reflecting on its application to artistic - pedagogical processes taking into account the point of view of the ensemble assembly teacher and the students who passed the subject, through semi-structured interviews. The opinion of the teacher Sandra Parra, the students interviewed and some authors was compared, determining that, within the formative evaluation, given in this subject, the coevaluation and the interest of the students were of great importance for a major advance in the process of creation.